All-Arthroscopic Refixation of an Osteochondral Femoral Avulsion of the Anterior Cruciate Ligament with a Laxity-Minimizing Suture - Horstmann H; Karkosch R; Plagge J; Smith T; Petri M (Dove Medical Press, 2023)
Hauke Horstmann, Roman Karkosch, Jochen Plagge, Tomas Smith, Maximilian Petri Department of Orthopedic Surgery, Hannover Medical School, Hannover, GermanyCorrespondence: Hauke Horstmann, Anna-von-Borries-Straße 1-7, Hannover, 30625, Germany, Tel +49 511 5354 568, Fax +49 511 5354 685, Email hauke.horstmann@diakovere.dePurpose: Torn anterior cruciate ligaments in children are rare injuries. The incidence of concomitant avulsion fracture in the skeletally immature patient is high. Reports of arthroscopic reconstruction in the literature are sparse.Case Presentation: We present the case of a femoral avulsion fracture of the anterior cruciate ligament in a seven-year-old girl. The patient underwent arthroscopic refixation with DynacordTM Suture and Suture Button. At a follow-up of 8 weeks, the patient had free range of motion and a stable knee, with a negative Lachman- and Pivot-Shift-test in particular.Conclusion: Refixation of femoral avulsion fracture can lead to good results. Open physes and size of the knee should be taken into account. Anatomic reconstruction is compulsory to receive bone on bone healing.Keywords: anterior cruciate ligament, femoral avulsion, arthroscopy, refixation